Global trends in Eastern Europe - Genov, Nikolai (Routledge, 2016)
Eastern Europe was once clearly defined by the centralized political and economic organization of the societies in the region. They shared the same official ideology and were members of the same alliances. After 1989, the region collapsed in an economic, political and cultural implosion. What were the moving forces of this profound change? What are its consequences? Could we try to reasonably foresee any future developments? In this thought-provoking book, Nikolai Genov presents a systematic description and explanation of Eastern European societal transformations after 1989. They are interpreted as adaptations to four global trends; upgrading the rationality of organizations; individualization; spreading of instrumental activism; and universalization of value-normative systems. Adaptations to these trends have generally been successful. However, Genov notes that the process is marked by many failures as well. They are mostly caused by path dependency in the societal development and by the varying quality of relevant decisions, other destructive developments are due to contradictions in the global trends themselves. Guided by the assumption that the societal and supranational integration mechanisms in Eastern Europe before 1989 could not resist the overwhelming power of global trends, Genov's controversial findings question visions about the end of history and simultaneously strengthen the confidence that most complex macro-social processes can be rationally managed. A timely book allowing for a much needed engagement in contemporary debates on the controversial processes in Eastern European transitions.